2015
DOI: 10.1099/vir.0.000039
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an intranasal immune response to human respiratory syncytial virus infection in cynomolgus macaques

Abstract: There is no large-scale therapy available against human respiratory syncytial virus (hRSV), a major pathogen responsible for acute respiratory diseases. Macaques represent an interesting animal model to evaluate potential treatments because of their genetic, anatomical and immunological proximity with humans. However, the parameters that influence hRSV growth and control in this model are still poorly understood. We have documented in the following study the influence of age as well as repeated infections on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This confirms our results in mice and cotton rats 40 and indicates that simple intramuscular prime-boost regimens using Adenoviral vectors are a robust approach to generating strong, cross-neutralizing and durable vaccine-mediated RSV-specific immunity that is able to migrate to the respiratory tract. As adult cynomolgus macaques are only semi-permissive to RSV without showing any clinical signs of disease 46 protective efficacy of the regimens was not assessed in this model. However, we previously demonstrated robust protective capacity of these vaccines against RSV-A2 and RSV B15/9 challenge in the permissive cotton rat model, compared with viral pre-exposure.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms our results in mice and cotton rats 40 and indicates that simple intramuscular prime-boost regimens using Adenoviral vectors are a robust approach to generating strong, cross-neutralizing and durable vaccine-mediated RSV-specific immunity that is able to migrate to the respiratory tract. As adult cynomolgus macaques are only semi-permissive to RSV without showing any clinical signs of disease 46 protective efficacy of the regimens was not assessed in this model. However, we previously demonstrated robust protective capacity of these vaccines against RSV-A2 and RSV B15/9 challenge in the permissive cotton rat model, compared with viral pre-exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Scientists have developed a rhesus monkey model of RSV infection and the studies based on the same have shown that the virus inoculum was directed to the upper airways only, whereas subsequent viral shedding was observed from both upper and lower respiratory tract secretions (Grandin et al 2016 ). Grandin et al ( 2015 ) created a Cynomolgus macaque model of mild infection using human RSV (hRSV), a common respiratory virus that causes infection in premature infants and children and is associated with high mortality when combined with other chronic diseases. This study showed that virological, clinical, and immunological parameters were also influenced by age and co-infection or morbidity (Grandin et al 2015 ).…”
Section: Inhalation Antibody Prophylaxis For Protection Against Respiratory Infectionsmentioning
confidence: 99%
“…1F) [44], [45], [46], [47], [48], [49], [50], [51]. Macaques are not very permissive for hRSV replication, and susceptibility to infection does not appear to be influenced by age [52]. Viral loads are usually determined by RT-PCR.…”
Section: Animal Models Of Rsvmentioning
confidence: 99%